Current Bladder Dysfunction Reports - Jaffe, William I.; Dmochowski, Roger R.; SpringerLink (Online service) (New York : Springer US : Imprint: Springer.)
The aim of this journal is to help readers understand expert views on current advances in the field of bladder dysfunction by systematically providing review articles that highlight the most important papers recently published. We accomplish this aim by appointing major authorities in key subject areas across the discipline to select topics reviewed by leading experts who emphasize recent developments, novel research, and highlight important papers published over the past year on their topics. We also highlight areas that have not received attention in the past and are important to an international audience, such a voiding dysfunction in reconstructed bladders and voiding dysfunction associated with genitourinary infections. An Editorial Board of internationally diverse members also suggests topics of special interest to their country/region and ensures that topics are current and include emerging research.
Keywords: Gynecology; Geriatrics; Urology; Urology; Geriatrics/Gerontology.; Gynecology